The emergence, importance of #DisabilityTooWhite hashtag - Mulderink, Carrie Elizabeth (Disability Studies Quarterly, 2020)
In this essay, I look at #DisabilityTooWhite (Thompson, 2016) as an activist call to center the messy intersectionality politics in the disability community, specifically in terms of disability and Whiteness. I center my theoretical commitments within the realm of DisCrit (Disability/Critical Race Theory) to critique the interplay of race (ism) and ability (ableism). I further utilize thematic textual analysis to study the content that has been posted by Twitter users under the #DisabilityTooWhite hashtag. I use an inductive approach to my analyses by drawing themes from my research that fall in line with DisCrit's central commitments as a means to deepen the conversations about disability, Whiteness, and social media.